Effects of Prior Knowledge on Comprehending Text About Learning Strategies - Kikas, Eve; Silinskas, Gintautas; Mädamürk, Kaja; Soodla, Piret (Frontiers in Education, 2021)
This study examined how reported use of learning strategies and preexisting beliefs about the effectiveness of rehearsal and comprehension-oriented strategies relate to the comprehension of text on learning strategies, and how text comprehension is related to later use of strategies and the completion of learning tasks. The participants were 2,706 students from Grades 3 and 4, and 3,782 students from Grade 9 across Estonia. Students’ learning strategies and learning outcomes were assessed via a web-based word list memorization task. The text was specifically developed to explain the advantages of abstract grouping. It was found that valuing comprehension-oriented strategies supported text comprehension at both grade levels, thereby demonstrating the importance of prior beliefs in text comprehension. Student beliefs and text comprehension also played a role in strategy use. However, students who used comprehension-oriented strategies showed ambiguous improvements in word memorization performance.